2021
DOI: 10.2147/idr.s303860
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Tract Colonization Rate of Extended-Spectrum Beta-Lactamase-Producing Gram-Negative Bacteria and Associated Factors Among Orthopaedic Patients in a Tertiary Hospital in Tanzania: Implications for Infection Prevention

Abstract: Background:The dual burden of road traffic accidents and antimicrobial resistance in orthopaedic infections is challenging already strained health-care systems. Limited information exists in Tanzania on antimicrobial resistance surveillance to delineate the potential sources of multidrug-resistant bacteria for specific mitigation strategies among orthopaedic patients. Methods: A longitudinal study was conducted at Bugando Medical Centre in Mwanza city between January and May 2020. It involved the collection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The study population constituted of whole-genome sequence data obtained from a total of 142 multi-drug resistant E. coli bacterial isolates provided by the mother study titled, “Understanding Transmission Dynamics and Acquisition of Antimicrobial Resistance at Referral Hospitals and Community Settings in East Africa using Conventional Microbiology and Whole-Genome Sequencing”. The multi-drug isolates were collected from both study sites in Uganda (n = 57) and Tanzania (n = 85) from patients, the immediate non-medical caretakers of these patients, the immediate health workers attending to these patients and the patients’ environment as previously discussed in detail by the recent publications from Uganda [ 1 ] and Tanzania [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study population constituted of whole-genome sequence data obtained from a total of 142 multi-drug resistant E. coli bacterial isolates provided by the mother study titled, “Understanding Transmission Dynamics and Acquisition of Antimicrobial Resistance at Referral Hospitals and Community Settings in East Africa using Conventional Microbiology and Whole-Genome Sequencing”. The multi-drug isolates were collected from both study sites in Uganda (n = 57) and Tanzania (n = 85) from patients, the immediate non-medical caretakers of these patients, the immediate health workers attending to these patients and the patients’ environment as previously discussed in detail by the recent publications from Uganda [ 1 ] and Tanzania [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, during prolonged hospitalization, susceptible bacteria may acquire resistant gene through conjugation mechanism or through genetic mutation [7]. There are many factors that can facilitate the colonization rate of MDRB in hospitalized patients: such as low hygiene practice, improper antibiotic usage, prolonged hospitalization, implanted materials, sharing a single room with high carrier patients including door knobs, wheelchairs and sinks have been associated [8][9][10]. In addition, patients may remain colonized by MDRB after they leave the hospital and become a potential source of resistant gene transmission for the community [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in Tanzania observed an increase in the prevalence of MDR bacteria causing infections and colonization of healthy populations [ [15] , [16] , [17] , [18] ]. The prevalence of fecal carriage of ESBL-PE in Tanzania ranges between 30% and 50% in hospitals and communities [ [17] , [18] , [19] , [20] , [21] ]. Studies have reported the isolation of MRSA and ESBL-PE in bloodstream infections [ 15 , 16 ], surgical site infections [ 22 , 23 ], and urinary tract infections [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%